Friction Durability and Nanowear of Extremely thin Diamond-Like Carbon Films Dependence on Film Thickness - Shojiro Miyake; Masatoshi Miyake (Science and Technology: Developments and Applications Vol. 6, 2025)
Nanotribology is a key technology for the advanced mechanical industry. The development of advanced micro- and nano-mechanical systems, bio-technology elements, automobile mechanics and so on have been realized in recent years. Nanotribology is a key technology for the advanced mechanical industry. The development of advanced micro- and nano-mechanical systems, bio-technology elements, automobile mechanics and so on have been realized in recent years. Tribological durability properties of extremely thin diamond-like carbon (DLC) films (target thickness 0.03–5 nm) deposited using filtered cathodic vacuum arc (FCVA) and plasma-chemical vapor deposition (P-CVD) methods were evaluated using load-increase-and-decrease, ball-on-disk, and low-load reciprocating friction tests. Friction durability notably increased at a certain film thickness for FCVA-DLC and P-CVD-DLC films. These thicknesses were nearly equal to surface roughness and corresponded to film thickness at which the nanowear profiles changed from protuberance to grooves and at which nanoscratch resistance increased. Excellent friction durability of FCVA-DLC films (thickness \(\) 0.4 nm), evaluated by the rapid increase in the friction coefficient, was observed. In contrast, the friction durability of P-CVD-DLC films gradually increased when the film thickness was 0.6 nm or greater. When the thickness of the DLC films was 2.0 nm or greater, the films did not exhibit a rapid increase in their friction coefficient within the total number of testing cycles. The tribological properties of extremely thin DLC films depend on film thickness; extremely thin FCVA-DLC films exhibit excellent wear resistance. The film thickness at which FCVA-DLC films endured the total number of test cycles was approximately one-fifth the corresponding thickness of P-CVD-DLC films, evaluated by the three different friction tests. The friction durability notably increases at a certain film thickness. FCVA-DLC films (thickness \(\) 0.4 nm) exhibited excellent friction durability. The ratio between the durable film thickness of FCVA-DLC and P-CVD-DLC films was about 1/5. Friction durability dependence on thickness corresponds to the nanowear properties.